The Preparation of Virgin Coconut Oil Using Acid from Passion Fruit Extract at Different Temperature and Incubation Time - Ayuningtyas, Inggrit Pangestu; Broto, Wisnu (Journal of Applied Food Technology, 2023)
Virgin coconut oil (VCO) is a liquid coconut product with a translucent color, a characteristic coconut aroma, and long shelf life. VCO can be made in various ways, including enzymatic, centrifugation, acidification, etc. In this study, the acidification method was used to manufacture VCO whereby the acid used is sourced from passion fruit. This study aims to determine the effect of passion fruit juice addition on the preparation virgin coconut oil. Several variables were employed in the current study, including passion fruit volume of 5 and 8 ml, incubation time of 12 hours and 24 hours, and incubation temperature of 36 and 48 °C in a Factorial Design. The amount of coconut was 660 grams and 660 ml distilled water. The results showed that the production temperature greatly influenced the free fatty acids produced. The best treatment was obtained on VCO with 8 ml passion fruit addition, 12 hours of formation time and 48°C incubation temperature, with 0.12% free fatty acids.